William and the mouse - Poulton, Mike; Brychta, Alex Silver, Maggie Englander, Alice Clifford, Rowan (Oxford University Press, 1988)
William and the Mouse is a delightful children's story about a young boy named William who forms an unlikely friendship with a small, clever mouse. The tale begins when William discovers the mouse in his home and, instead of trying to get rid of it, he befriends the little creature. As their bond grows, the mouse helps William navigate various challenges, from solving small household problems to learning important life lessons about empathy, kindness, and understanding. Through this friendship, William comes to appreciate the value of looking at the world from a different perspective, highlighting themes of acceptance and compassion.